Ninth Five Year Plan 1997-2002 Volume-VI General Areas Government of Assam - Planning Commission (Planning Commission, 1997)
The Eight Five year plan originally provided an allocation of Rs.12308.00 Lakhs excluding Medical Education sector. But cumulative plan allocation for five years stand Rs. 17774.80 lakhs and the total expenditure including the anticipated expenditure in 1996-97 in real terms is Rs. 13601.92 lakhs. The expenditure under minimum needs programme now known as "Basic Minimum Services" was Rs. 6944.42 lakhs. This programme was the priority sector during the 8th Plan. The activities under MNP are also covered by the "20 Point Programme" of the Govt. of India.
Planning and Development Department, Government of Assam
Planning and Development Department, Government of Assam